Sophie hits six - King-Smith, Dick. (Candlewick Press, 1993)
The year that Sophie turns six, she sees her cat give birth to kittens, gets a pet rabbit from her Aunt Al, and pursues her dream of acquiring a dog. Sequel to "Sophie's Snail" and "Sophie's Tom."